Serial Production of Domestic Biologically Active Glue for Medical Purposes - Lebedev, Ye.V.; Galatenko, N.A.; Rozhnova, R.A.; Kulesh, D.V. (Science and Innovation, 2024)
New domestic biologically active medical glue has been developed for the application to implantation, dermatoplasty, bonding or fixation of soft tissues and bones, as well as for the stimulation of regeneration process. Comprehensive biomedical research, preclinical, clinical, and certification tests have been carried out. Technical documentation has been prepared and approved. Serial production of medical glue has been organized at the Medical Polymers Department of the Institute for Chemistry of High-Molecular Compounds of the NAS of Ukraine.